1986
DOI: 10.1152/ajpregu.1986.251.2.r250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors involved in determining urinary bladder voiding cycle in urethan-anesthetized rats

Abstract: The mechanism(s) involved in determining the voiding cycle of the rat urinary bladder have been investigated in urethan-anesthetized animals. Fluid emission is almost confined to that phase of the voiding cycle which is characterized by the presence of a series of high-frequency oscillations in intraluminal pressure (IPHFO). During this phase the mean urethral flow rate reached a maximum and fluid was expelled in a stream-like fashion. The index obtained by multiplying the amplitude of IPHFO by their duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 0 publications
8
125
3
Order By: Relevance
“…Pharmacological inhibition of the EUS with the preserved function of the detrusor is sufficient to achieve some voiding. However, the bursting activity of the EUS is necessary for complete emptying of the rat bladder (Maggi et al, 1986;Mersdorf et al, 1993;Kakizaki et al, 1997). Interestingly, our results show a positive correlation between voiding efficiency and the number of surviving motoneurons but not PPNs in the implanted series, emphasizing the role and importance of functional innervation of striated sphincter and pelvic muscles by somatic motoneurons for efficient voiding.…”
Section: Activation Of the Detrusor And Eus Musclesmentioning
confidence: 56%
See 1 more Smart Citation
“…Pharmacological inhibition of the EUS with the preserved function of the detrusor is sufficient to achieve some voiding. However, the bursting activity of the EUS is necessary for complete emptying of the rat bladder (Maggi et al, 1986;Mersdorf et al, 1993;Kakizaki et al, 1997). Interestingly, our results show a positive correlation between voiding efficiency and the number of surviving motoneurons but not PPNs in the implanted series, emphasizing the role and importance of functional innervation of striated sphincter and pelvic muscles by somatic motoneurons for efficient voiding.…”
Section: Activation Of the Detrusor And Eus Musclesmentioning
confidence: 56%
“…In the normal adult rat, storage is dependent on the inhibition of parasympathetic action on the smooth bladder muscle (detrusor) and on the sympathetic tonic activation of the internal urethral sphincter for outflow resistance. During micturition, efficient voiding is dependent on synchronous activation of the detrusor for contraction, relaxation of the internal urethral sphincter, and bursting activity of the striated external urethral sphincter (EUS) for enhanced urine flow (Maggi et al, 1986;Kruse et al, 1993). Normal control of bladder function involves a complex interaction between the cerebral cortex, pontine micturition center, sympathetic and parasympathetic nervous systems, and somatic motoneurons in the lumbar spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few articles detailing differences between females and males in the lower urinary tract functions. Of the available reports, for example, one previous study comparing female and male rats in cystometry revealed that volume thresholds for inducing micturition were changed in accordance with altered intravesical infusion rates in the female rat, whereas these were constant regardless of the bladder filling rates in the male (24). The study suggested the possibility that mechanosensory afferent responses to intensity of the mechanical stimulus were different between the female and male animals.…”
mentioning
confidence: 85%
“…Decerebration, which removes the forebrain receiving signals from the peripheral organs and supplying both excitatory and inhibitory inputs to the brain stem, has been established for in vivo urological research (27,40,41,(45)(46)(47)(52)(53)(54)(55)(56) and allows the study of involuntary "reflex" activity of the lower urinary tract as the brain stem (i.e., including periaqueductal gray and pons), spinal cord (i.e., including thoracic sympathetic neurons and lumbosacral parasympathetic neurons), and peripheral nerves in which neural circuits responsible for voiding and storage (12) are intact. On the other hand, conscious (9,18,43,49,50) and anesthetized (14,24,26,42,48,51,57,58) rodents are mainstays for in vivo studies. Voluntary micturition "behavior" in conscious animals, however, can be affected by stress from circumstances (31,36) or drugs that change the mood of the animal (37,44), and thus greater attention should be paid to the use of the model.…”
Section: Ajp-regul Integr Comp Physiolmentioning
confidence: 99%
“…For this purpose, we performed an expanded analysis of the above CMG and EUS EMG recordings, taking into consideration also different aspects of the functional state of the lower urinary tract (LUT). For instance, special attention was paid to the bladder expulsion phase, indicated by a period of high frequency oscillations (HFO), which normally takes place during a bladder contraction and is detectable during CMG recordings (Maggi et al, 1986a). Bladder distension at volumes below the threshold for evoking micturition elicits high frequency tonic activity of the EUS, whereas bladder distension at volumes sufficient to initiate micturition elicits a prolonged phasic activity of the EUS at lower frequencies between 6-8 Hz in the rats.…”
Section: Introductionmentioning
confidence: 99%